2016
DOI: 10.1016/j.numecd.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Increases in plasma plant sterols stabilize within four weeks of plant sterol intake and are independent of cholesterol metabolism

Abstract: Increases in plasma PS stabilize within 4 weeks of PS intake and do not seem impacted by basal cholesterol synthesis or absorption efficiency. This study was registered at clinicaltrials.gov (NCT01803178).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Chemical structure of stigmasterol is shown in Figure 1A. It has been widely used in traditional Chinese medicine and food industry due to its various important bioactivities 13,14. For example, literature have well demonstrated that stigmasterol can act as the precursors of corticoids-1, progesterone, androgens, estrogens and vitamin D 3 , and easily pass blood–brain barrier 15,16.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical structure of stigmasterol is shown in Figure 1A. It has been widely used in traditional Chinese medicine and food industry due to its various important bioactivities 13,14. For example, literature have well demonstrated that stigmasterol can act as the precursors of corticoids-1, progesterone, androgens, estrogens and vitamin D 3 , and easily pass blood–brain barrier 15,16.…”
Section: Introductionmentioning
confidence: 99%
“…This study was part of the INVEST study (INvestigating Vascular function Effects of plant STerols) which was primarily designed to investigate the effect of a low-fat spread with added PS on FMD, and also measured arterial stiffness (pulse wave velocity and augmentation index), blood pressure, serum lipids and plasma PS concentrations ( 10 , 25 ) .…”
mentioning
confidence: 99%
“…Ras and colleagues (2016) showed that consumption of a low-fat spread with added plants sterols (3 g/day) increases plasma concentrations of sitosterol and campesterol in the first four weeks, while no further increases were observed in the following eight weeks of consumption. However, concentrations at the end of the intervention did not exceed physiological values usually observed in the general population (2.8 to 27.9 µmol/L) [46]. Competition between plant sterols and free cholesterol during digestion causes a reduction in cholesterol solubilization and increases cholesterol excretion in feces.…”
Section: Plant Sterolsmentioning
confidence: 73%